2020
DOI: 10.1101/2020.08.04.236521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lymphopenia-induced T cell proliferation is a hallmark of severe COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has a broad clinical presentation ranging from asymptomatic infection to fatal disease. Different features associated with the immune response to SARS-CoV-2, such as hyperinflammation and reduction of peripheral CD8+ T cell counts are strongly associated with severe disease. Here, we confirm the reduction in peripheral CD8+ T cells both in relative and absolute terms and identify T cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…SARS-CoV mouse models have shown that the recruitment of proinflammatory monocytes to the lungs, promoted by delayed type I IFN signaling, drives immunopathology, and interestingly, a scRNA-seq study in bronchoalveolar lavage fluid of SARS-CoV-2 infected individuals found an accumulation of monocyte-derived macrophages and high levels of inflammatory cytokines in severe patients. 16 , 22 Several factors, such as a maladapted IFN response or an inadequate T cell response in severe COVID-19, 46 may contribute to the dysregulated monocyte response in severely ill patients. The latter could be due to suboptimal viral control, although T cells have also been shown to control an overactive innate response in a murine coronavirus infection model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV mouse models have shown that the recruitment of proinflammatory monocytes to the lungs, promoted by delayed type I IFN signaling, drives immunopathology, and interestingly, a scRNA-seq study in bronchoalveolar lavage fluid of SARS-CoV-2 infected individuals found an accumulation of monocyte-derived macrophages and high levels of inflammatory cytokines in severe patients. 16 , 22 Several factors, such as a maladapted IFN response or an inadequate T cell response in severe COVID-19, 46 may contribute to the dysregulated monocyte response in severely ill patients. The latter could be due to suboptimal viral control, although T cells have also been shown to control an overactive innate response in a murine coronavirus infection model.…”
Section: Discussionmentioning
confidence: 99%
“…Routine flow cytometry for NK cell quantification was performed on all samples in the accredited immunological laboratory at the University Hospital Zurich, as previously described. 46 The cohort characteristics and a selection of the Olink dataset are also shown in Adamo et al. 46 describing the T cell response of this cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests an important relationship between pathogenesis and the circulating T cell pool. Observed lymphopaenia in adult COVID-19 patients is likely to be multifactorial in origin, with redistributive effects, apoptotic loss [ 74 ], and possibly reduced mobilisation of lymphocytes from bone marrow, all playing a part. Prior work has also shown an association between IL-6 production and blockade of lymphopoiesis; although the extent to which this mechanism operates in COVID-19 has yet to be investigated [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive arm of the immune system appears to be crippled with significant T cell loss or lymphopenia (especially CD8 + T cells) in the peripheral blood of severe patients‐ both due to extensive apoptosis (preferentially of CD8 + T cells) as well as T cell migration to the lungs (Adamo et al, 2020). Despite the significant T cell loss, highly activated peripheral T cells were found in a subgroup of hospitalized COVID‐19 patients, and T cell activation was associated with more severe disease and organ failure (Mathew et al, 2020).…”
Section: An Integrated View Of Disease Fueled By Immune Profilingmentioning
confidence: 99%